A round‐robin evaluation of the repeatability and reproducibility of environmental DNA assays for dreissenid mussels. Issue 4 (13th January 2020) - Sepulveda, Adam J.; Hutchins, Patrick R.; Jackson, Craig; Ostberg, Carl; Laramie, Matthew B.; Amberg, Jon; Counihan, Tim; Hoegh, Andrew; Pilliod, David S.
Abstract: Resource managers may be hesitant to make decisions based on environmental (e)DNA results alone since eDNA is an indirect method of species detection. One way to reduce the uncertainty of eDNA is to identify laboratory‐based protocols that ensure repeatable and reproducible results. We conducted a double‐blind round‐robin analysis of probe‐based assays for DNA of dreissenid ( Dreissena spp.) mussels, which are prolific aquatic invaders that can cause significant economic and ecological impacts. DNA extract from water samples spiked with known amounts of dreissenid DNA and from water samples collected from waters with and without dreissenids were analyzed by four independent research laboratories. We used results to calculate detection repeatability within laboratories and assays, detection reproducibility among laboratories and assays, and estimated dreissenid DNA copy number precision and accuracy. Laboratory and assay repeatability and reproducibility of detection results were high, 91% and 92%, respectively. The estimated copy numbers were neither precise nor accurate for samples spiked with <773 gene copies. These results suggest that eDNA surveillance of dreissenid mussels, using the protocols evaluated herein, can generate reliable detection data for decision‐making. However, managers should be cautious about using the quantitative information often associated with eDNA detections, especially when DNA is at lower abundance. Our results provide strong support that eDNA has the potential to provide repeatable and reproducible evidence under varying laboratory conditions and for different sample water chemistries. This is reassuring since the demand for eDNA surveillance is widespread and number of laboratories that process eDNA samples is growing steadily. Abstract : We conducted a double‐blind round‐robin analysis of probe‐based assays for DNA of dreissenid ( Dreissena spp.) mussels, which are prolific aquatic invaders that can cause significant economic and ecological impacts. We used results to calculate detection repeatability within laboratories and assays, detection reproducibility among laboratories and assays, and estimated dreissenid DNA copy number precision and accuracy. Laboratory and assay repeatability and reproducibility of detection results were high, 91% and 92%, respectively, but the estimated copy numbers were neither precise nor accurate for samples spiked with <773 gene copies.